SOIL CHARACTERIZATION AND NUTRIENT COMPOSITION OF MANGROVE VEGETATION IN CARMEN, CEBU - Piquero, Alfonso S; Delan, Gloria G; Rica, Rachel Luz V; Corrales, Christine M; Lamayo, Ma. Helian M (Journal of Agriculture and Technology Management, 2015)
Mangrove soils are estuarine and marine alluvium transported and deposited as sediments and nutrient particles through the influence of tidal inundation by rivers and seas. This study was conducted to characterize soil and quantify nutrient load to understand mangrove vegetation recruitment and structure. Using a 50 meter transect line, soil samples were collected, from the 6 coastal barangays of Carmen, Cebu, namely: Puente, Luyang, Dawis Norte, Dawis Sur, Cogon East and Poblacion. The soils were air dried, crushed and subjected to laboratory analyses. Other parameters were measured in situ within the study area. Results revealed that soil acidity, water temperature and water salinity in the area are desirable for the growth of mangroves. Low D.O was observed in all the sites which indicates high pollution level. Loam type of mangrove soil texture with high concentration of nutrients and organic matter were observed. Finding of the study suggest that soil characteristics and nutrient load could be an attribute to the abundance and diversity of mangrove vegetation.